Impact of COVID-19 pandemic on catheter ablation in China: A spatiotemporal analysis - Jiang, Jiang; Zhao, Shuang; Cheng, Chendi; Lin, Na; Li, Ping; Ning, Xiaohui; Zhang, Shu (Frontiers in Public Health, 2022)
Background: The COVID-19 pandemic has significantly impacted routine cardiovascular health assessments and services. We aim to depict the temporal trend of catheter ablation (CA) and provide experience in dealing with the negative impact of the COVID-19 pandemic. Methods: Data on CA between January 2019, and December 2021, were extracted from the National Center for Cardiovascular Quality Improvement platform. CA alterations from 2019 to 2021 were assessed with generalized estimation equation. Results: A total of 347,924 patients undergoing CA were included in the final analysis. The CA decreased remarkably from 122,839 in 2019 to 100,019 (−18.58%, 95% CI: −33.40% to −3.75%, p=.02) in 2020, and increased slightly to 125,006 (1.81%, 95% CI: −7.01% to 3.38%, p=.49) in 2021. The CA experienced the maximal reduction in February 2020 (−88.78%) corresponding with the peak of monthly new COVID-19 cases and decreased by 54.32% (95%CI: −71.27% to −37.37%, p<.001) during the 3-month lockdown and increased firstly in June 2020 relative to 2019. Since then, the CA in 2020 remained unchanged relative to 2019 (−0.06%, 95% CI: −7.01% to 3.38%, p=.98). Notably, the recovery of CA in 2021 to pre-COVID-19 levels was mainly driven by the growth of CA in secondary hospitals. Although there is a slight increase (2167) in CA in 2021 relative to 2019, both the absolute number and proportion of CA in the top 50 hospitals nationwide [53,887 (43.09%) vs 63,811 (51.95%), p<.001] and top 3 hospitals in each province [66,152 (52.73%) vs 72,392 (59.28%), p<.001] still declined significantly. Conclusion: The CA experienced a substantial decline during the early phase of the COVID-19 pandemic, and then gradually returned to pre-COVID-19 levels. Notably, the growth of CA in secondary hospitals plays an important role in the overall resumption, which implies that systematic guidance of secondary hospitals with CA experience may aid in mitigating the negative impact of the COVID-19 pandemic.